Atomistic Visualization of Mesoscopic Whole‐Cell Simulations Using Ray‐Casted Instancing. (20th August 2013) - Falk, Martin; Krone, Michael; Ertl, Thomas
<x xml:space="preserve">Abstract</x> Molecular visualization is an important tool for analyzing the results of biochemical simulations. With modern GPU ray casting approaches it is only possible to render several million of atoms interactively unless advanced acceleration methods are employed. Whole‐cell simulations consist of at least several billion atoms even for simplified cell models. However, many instances of only a few different proteins occur in the intracellular environment, which can be exploited to fit the data into the graphics memory. For each protein species, one model is stored and rendered once per instance. The proposed method exploits recent algorithmic advances for particle rendering and the repetitive nature of intracellular proteins to visualize dynamic results from mesoscopic simulations of cellular transport processes with implicit surfaces and triangular meshes. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>